Atorvastatin Decreases Renal Menaquinone-4 Formation in C57BL/6 Male Mice. Issue 3 (8th February 2019) - Harshman, Stephanie G; Shea, M Kyla; Fu, Xueyan; Grusak, Michael A; Smith, Donald; Lamon-Fava, Stefania; Kuliopulos, Athan; Greenberg, Andrew; Booth, Sarah L
ABSTRACT: Background: Menaquinone-4 (MK4), a vitamin K metabolite, is converted from phylloquinone through a process that requires intermediates of endogenous cholesterol production. Recent evidence suggests that MK4 is involved in kidney function. Objective: The purpose of this study was to determine the effect of atorvastatin treatment on MK4 formation in young and old male mice. Methods: C57BL/6 male mice (4-mo-old and 20-mo-old) were randomly assigned to either a diet containing 300 mg atorvastatin/kg with 3 mg phylloquinone/kg or a control diet containing 3 mg phylloquinone/kg for 8 wk. During week 8, all mice received deuterium-labeled phylloquinone in the diet. Labeled and unlabeled phylloquinone and MK4 in liver, kidney, brain, and intestine were measured by atmospheric pressure chemical ionization LC/MS. 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase gene expression was quantified by reverse transcriptase-PCR. Tissue MK4 and phylloquinone concentrations were compared between atorvastatin treatment groups with use of general linear models. Results: There was no age-treatment interaction on MK4 tissue concentrations. In atorvastatin-treated mice, total MK4 and percentage of deuterium-labeled MK4 in kidney were both approximately 45% lower compared to values in mice not given atorvastatin (all P  < 0.05). MK4 concentrations did not differ between groups in any other tissue measured. Conclusion: In male mice, atorvastatin reduced endogenous MK4 formation in the kidney, but not other organs. These observations are consistent with our hypothesis that cholesterol metabolism is involved in the generation of MK4. Further research is needed to understand potential regulatory mechanisms and the unique functions of MK4 in the kidney.